ANALISIS BIBLIOMETRIK EFEKTIVITAS AUDIT INTERNAL BIBLIOMETRIC ANALYSIS OF INTERNAL AUDIT EFFECTIVENESS - Djumartono Djumartono (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study aims to describe and identify recent developments in the effectiveness of internal audit through a bibliometric approach. Specifically, the research focuses on mapping the most productive and most cited authors, the countries with the highest contribution to publications, and the most influential institutions in the study of internal audit effectiveness. Methods: Bibliometric analysis was conducted using VOSviewer, based on data retrieved from the Scopus database, comprising 233 articles published between 2014 and 2020. Results: The analysis indicates that Mihret is the most cited author, with 170 citations across 38 articles. Meanwhile, Alzeban is identified as the most productive author, having published 43 articles that have collectively received 58 citations. In terms of country contribution, the United States is the most dominant, with 75 publications and a total of 2,105 citations. Furthermore, the University of Florida in the United States is the institution contributing the most to this topic, with three publications that have garnered 328 citations. Keywords : Bibliometric Analysis; Internal Audit Effectiveness; VOSviewer